Daluyong manggagawang Pilipino sa panahon ng globalisasyon - Ilagan, Bonifacio 1951- (IBON Foundation, Video Production Unit, 2001)
Documentary captures the impact of globalization on workers in the Philippines. No job security, union busting, violation of workers' rights and welfare are the lament of workers in the country who have been hit by globalization. They show that the way to fight globalization is through militant struggle.